Fabrication and characterization of chitosan (CS) and chitosan (CS) blended polyvinyl alcohol (PVA) membrane with polyethylene glycol (PEG) 600 as additive - Rais Hanizam, Madon (2008)
This research is about fabrication and characterization of flat sheet chitosan (CS) and chitosan (CS) blended polyvinyl alcohol (PVA) membrane with polyethylene glycol (PEG) 600 as additive. The main objective of this research is to fabricate high solute separation and flux membrane and also to determine the effect of PVA on membrane performance and morphology. The membrane were prepared by dry phase inversion method from casting solution containing PVA as polymer, CS as functional polymer, formic acid as solvent and PEG 600 as additive. The membranes were characterize in terms of pure water permeation (PWP), solute separation (R), flux (J) and membrane morphology by observation using scanning electron microscopy (SEM) and atomic force microscopy (AFM). The results for PWP, the membrane contain PVA obtained the highest PWP value because PVA give drastic effect in terms of hydrophilic. For the solute separation (R%) and flux (J), the membrane contains PVA yield the highest value for both characterization. This is because the PEG help to form pores for the membrane. By SEM observation found that the membrane that contain PVA give clearly view of pores. This contributes to high flux and pure water permeation. Lastly, by AFM analysis, it shows that the roughness parameter of membrane was effected by the PVA concentration. The membrane contains PVA show more rough surface because the nodules is not merge. From this research, can be conclude that PVA has become the solution to achieve both high selectivity and permeability in membrane.